1998
DOI: 10.1088/0022-3727/31/13/007
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and corrosion resistance of Nd-Fe-B magnets containing additives

Abstract: The oxidation behaviour of the phase in Nd-Fe-B sintered magnets containing additional elements (Al, Co, V, Nb, Mo) was investigated by Mössbauer spectrometry. The microstructure of the different samples was first characterized. Added elements were detected in both intergranular and intragranular precipitates. The presence of X-Fe-B (, V, Mo) precipitates was evidenced by high-resolution scanning electron microscopy, x-ray diffraction and Mössbauer spectrometry. The presence of Al and Co substituted to Fe in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…However, for the DCVA, CVA and CMA samples, the α-Fe contribution is characterized by a higher mean hyperfine field (34.6-34.7 T) than that obtained for the Nd 16 Fe 76 B 8 and DNA samples (33.3-33.4 T). This is attributed to the presence of Co in the α-Fe phase, in agreement with the fact that Co atoms substitute for Fe atoms in the Nd 2 Fe 14 B unit cell [27]. By interpolating the results of a study of the mean hyperfine field in Fe 1−x Co x compounds (with 0 x 0.5) [28], the Co content in α-Fe was estimated to be 8 at.%.…”
Section: Oxidized Nd-fe-b Powders Containing Additivessupporting
confidence: 68%
See 2 more Smart Citations
“…However, for the DCVA, CVA and CMA samples, the α-Fe contribution is characterized by a higher mean hyperfine field (34.6-34.7 T) than that obtained for the Nd 16 Fe 76 B 8 and DNA samples (33.3-33.4 T). This is attributed to the presence of Co in the α-Fe phase, in agreement with the fact that Co atoms substitute for Fe atoms in the Nd 2 Fe 14 B unit cell [27]. By interpolating the results of a study of the mean hyperfine field in Fe 1−x Co x compounds (with 0 x 0.5) [28], the Co content in α-Fe was estimated to be 8 at.%.…”
Section: Oxidized Nd-fe-b Powders Containing Additivessupporting
confidence: 68%
“…The nominal atomic compositions of the samples containing additives (DCVA, CVA, CMA and DNA) are reported in table 1. The microstructural investigation of these samples is reported elsewhere [27]. This study revealed the presence of both intergranular and intragranular Layer composed of: Layer composed of: X-Fe-B precipitates (with X = V, Nb, Mo).…”
Section: Oxidized Nd-fe-b Powders Containing Additivesmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, considerable effort has been devoted to enhancing the corrosion resistance of NdFeB magnets using surface coating such as electroplating of Ni, electroplating of Zn, and spraying of epoxy resin [1][2][3][4]. In parallel, the attempts have been made to improve the corrosion resistance NdFeB alloys by addition of other alloying elements, including Pb, Ti, Zr, Sn and Cr [5][6][7][8]. The addition of these elements, however, is likely associated with the degradation of magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…First studies revealed that nanocrystalline magnets have a higher environmental susceptibility than sintered microcrystalline magnets and that their corrosion behaviour depends strongly on the powder processing route generating different grain sizes. Other rare earth elements (Dy, Pr), transitional elements (Co, Ni) or metals (Ga and/or Al) are suitable additives for improving the magnetic properties and corrosion resistance, as reported in literature [18][19][20].…”
Section: Introductionmentioning
confidence: 89%